Design and preparation of bi-functionalized short-chain modified zwitterionic nanoparticles. (May 2018) - Hu, Fenglin; Chen, Kaimin; Xu, Hong; Gu, Hongchen
Graphical abstract: Abstract: An ideal nanomaterial for use in the bio-medical field should have a distinctive surface capable of effectively preventing nonspecific protein adsorption and identifying target bio-molecules. Recently, the short-chain zwitterion strategy has been suggested as a simple and novel approach to create outstanding anti-fouling surfaces. In this paper, the carboxyl end group of short-chain zwitterion-coated silica nanoparticles (SiO2 -ZWS) was found to be difficult to functionalize via a conventional EDC/NHS strategy due to its rapid hydrolysis side-reactions. Hence, a series of bi-functionalized silica nanoparticles (SiO2 -ZWS/COOH) were designed and prepared by controlling the molar ratio of 3-aminopropyltriethoxysilane (APTES) to short-chain zwitterionic organosiloxane (ZWS) in order to achieve above goal. The synthesized SiO2 -ZWS/COOH had similar excellent anti-fouling properties compared with SiO2 -ZWS, even in 50% fetal bovine serum characterized by DLS and turbidimetric titration. Subsequently, SiO2 -ZWS/COOH5/1 was chosen as a representative and then demonstrated higher detection signal intensity and more superior signal-to-noise ratios compare with the pure SiO2 -COOH when they were used as a bio-carrier for chemiluminescence enzyme immunoassay (CLEIA). These unique bi-functionalized silica nanoparticles have many potential applications in the diagnostic and therapeutic fields. Statement of significance: Reducing nonspecific protein adsorption and enhancing the immobilized efficiency of specific bio-probes are two of the most important issues for bio-carriers, particularly for a nanoparticle based bio-carrier. Herein, we designed and prepared a bi-functional nanoparticle with anti-fouling property and bio conjugation capacity for further bioassay by improving the short-chain zwitterionic modification strategy we have proposed previously. The heterogeneous surface of this nanoparticle showed effective anti-fouling properties both in model protein solutions and fetal bovine serum (FBS). The modified nanoparticles can also be successfully functionalized with a specific antibody for CLEIA assay with a prominent bio-detection performance even in 50% FBS. In this paper, we also investigated an unexpectedly fast hydrolysis behavior of NHS-activated carboxylic groups within the pure short-chain zwitterionic molecule that led to no protein binding in the short-chain zwitterion modified nanoparticle. Our findings pave a new way for the designing of high performance bio-carriers, demonstrating their strong potential as a robust platform for diagnosis and therapy.